Agency cost of Shariah governance and impact on fund value in Malaysia - Sofi, Mohd Fikri (2018)
The mutual fund has become an increasingly important investment vehicle for retail investors, especially among households. Besides developing an institutional investment as efficient momentum trader and information extractor, separation of ownership and control prevails within a mutual fund contract during asset movement to fund management given an expected level of return by investors. The unobserved activities and widely magnitude decision skills of managers with the tendency of self-interest distress the shareholders, predominantly in Shariah Mutual Fund (SMF), pertaining to conflicting dual investing interests. High concern on fund value by performance is equally important that all generating return incomes are engendered from activities and course of actions that are in accordance to Shariah principle. This study aims to examine the effectiveness of multiple internal governance control mechanisms comprising ownership concentration, the board structure, and fund fees, especially when additional governance of Shariah Advisory Panel (SAP) emerges in a complex governance structure of fund management between Shariah and conventional within principal-agent relationship. Moreover, the objective also devotes on measuring SAP material to agency cost and the linking relationship. An assortment of data attributes to mutual fund is obtainable from published annual reports, while other data, such as monthly dividend adjusted Net Asset Value (NAV) and monthly market index return are possibly retrieved from Datastream to measure fund value market return. Dynamic panel data regression is employed to generate model that best explains unbiased estimation controlling for many recent econometric issues, such as endogeneity to avoid spurious evidence. The main finding indicates a significant association of Shariah governance with agency cost despite the absence in difference for a greater level of agency cost in such a more complex governance structure fund. However, there is only little or weak evidence between the relation of Shariah governance and fund value Nevertheless, the coefficients direction are consistently negative following an increase in fund operational expenses.